State Bar Annual Meeting at Town and Country Hotel San Diego - Watkins, Howard::::::::: (1985)
Estate Planning workshop with Danny Santucci, Leslie Shapiro, Martin Schainbaum, Benjamin Sanchez, Mark Ancel and Fresno's John McGregor